2015
DOI: 10.1007/s10008-015-2926-4
|View full text |Cite
|
Sign up to set email alerts
|

Poly(thionine)-carbon nanotube modified carbon film electrodes and application to the simultaneous determination of acetaminophen and dipyrone

Abstract: Multi-walled carbon nanotube (MWCNT)-poly(thionine) (PTH) nanostructures were formed on carbon film electrodes (CFE), the polymer film being formed beneath or on top of MWCNT, to give two different sensor architectures, PTH/MWCNT/CFE or MWCNT/PTH/CFE. Characterization of the novel nanostructures was carried out by cyclic voltammetry, electrochemical impedance spectroscopy and scanning electron microscopy. The modified electrodes were then used for sensing acetaminophen (ACOP) and dipyrone by differential pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…As far as we know, these have never been used for acetaminophen determination. Nevertheless, the obtained DL in this work is very close to that reported (0.83 × 10 −6 mol dm −3 ) for a similar study with a MnFe 2 O 4 @N-CNT [36] nanocomposite or with other carbon-based modified electrodes (Table 3)[ 32, 49, 50]a n d better than those obtained for poly(thionine) and poly(methylene green)/multi-walled carbon nanotube (MWCNT) modified electrodes [51,52]. The only sensor with better results was the N-MWCNTs/AuNPs [53] with a DF = 0.35 × 10 −6 mol dm −3 ; however, this involved the use of gold nanoparticles which is less cost-effective and requires more complex sensor architecture.…”
Section: Electrocatalytic Sensing Performance Of Nanocomposite Modifisupporting
confidence: 89%
“…As far as we know, these have never been used for acetaminophen determination. Nevertheless, the obtained DL in this work is very close to that reported (0.83 × 10 −6 mol dm −3 ) for a similar study with a MnFe 2 O 4 @N-CNT [36] nanocomposite or with other carbon-based modified electrodes (Table 3)[ 32, 49, 50]a n d better than those obtained for poly(thionine) and poly(methylene green)/multi-walled carbon nanotube (MWCNT) modified electrodes [51,52]. The only sensor with better results was the N-MWCNTs/AuNPs [53] with a DF = 0.35 × 10 −6 mol dm −3 ; however, this involved the use of gold nanoparticles which is less cost-effective and requires more complex sensor architecture.…”
Section: Electrocatalytic Sensing Performance Of Nanocomposite Modifisupporting
confidence: 89%
“…In general, the LOD values achieved in our study are higher than most of the data found in the literature. As can be seen in Table S3, the LODs reported in the literature for paracetamol, metamizole and midazolam ranged between 10 −5 −10 −10 mol L −1 , 10 −5 −10 −8 mol L −1 , and 10 −5 −10 −7 mol L −1 , respectively. On the other hand, the detectability levels obtained for metamizole and midazolam using ePADs were slightly better than those found in two reports.…”
Section: Resultsmentioning
confidence: 94%
“…While the performance of the ePADs is below other references , two advantages need to be highlighted. First, ePADs were prepared and used without any modification with nanomaterials or charge transfer mediators.…”
Section: Resultsmentioning
confidence: 99%
“…Multiwalled carbon nanotubes (MWCNT) also possess outstanding characteristics, including good electrical conductivity, high mechanical strength and modulus, high chemical stability, large adsorption ability and catalytic properties . Furthermore, they can be an ideal matrix to interact with various inorganic and organic molecules, an advantageous property in the design and development of modified electrode electrochemical sensors .…”
Section: Introductionmentioning
confidence: 99%